Taskforce framework in validating authenticity of university information over the wikipedia / Hayati Abd Rahman … [et al.] - Abd Rahman, Hayati; Mohd Noor, Zainab; Abd Rashid, Amirul; Mohd Janor, Roziah (Universiti Teknologi MARA, 2022)
Wikipedia is considered a globally primary resource for public review. As it is the largest, free, and most popular general reference work on the World Wide Web, it is easy for web crawlers to do their search indexes and improve the visibility of the page in the digital world. To sustain its top ranking in organic search and display of any search engines, Wikipedia attracts many links and contains a large amount of content on a broad set of topics. Document about Universiti Teknologi MARA (UiTM) started in Wikipedia since 2004, and it has been consistently evolving since then. UiTM has many branch campuses throughout the nation. It is Malaysia's largest institution of higher learning in terms of size and population, with the anchor campus in Shah Alam and one in each state. Whilst the main university is visible digitally, the branch campuses are almost invisible digitally. These may lead to inauthentic content and dispute of affiliation among the UiTM branches. This paper discusses the approach taken to overcome the problem of the authenticity of facts about UiTM. Content analysis is deployed throughout all related campus pages found on Wikipedia. A table of guideline was developed to form an authenticity checklist.